2021
DOI: 10.1159/000512920
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Can Contribute to Severe Persistent Allergic Rhinitis in Children through Leptin and Interleukin-1β

Abstract: Background: Obesity/overweight is associated with a higher risk of allergic rhinitis (AR) in children. Objective: This study aimed at exploring the mechanisms by which obesity affects the severity of AR through leptin and interleukin (IL)-1β were investigated. Methods: In all, 210 subjects with AR and 82 subjects without AR were included in this study. The levels of leptin and inflammatory biomarkers were measured in the serum to investigate the correlation with the severity of AR. Additionally, we analyzed wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 28 publications
(29 reference statements)
1
16
1
Order By: Relevance
“…Evidence indicated that leptin could activate eosinophils to markedly induce the release of in ammatory cytokines, such as IL-β, TNF-α, etc. Also, the elevating of leptin levels also may aggravate the severity of ECRS, promote and enhance systemic type 2-biased in ammatory response as well as the development of eosinophilic in ammation in nasal polyps [51,62,63]. While Kanagalingam S et al pointed out that obesity did not affect the severity of sinonasal diseases in asthma patients, which is paradoxical with our results [64].…”
Section: Discussioncontrasting
confidence: 75%
“…Evidence indicated that leptin could activate eosinophils to markedly induce the release of in ammatory cytokines, such as IL-β, TNF-α, etc. Also, the elevating of leptin levels also may aggravate the severity of ECRS, promote and enhance systemic type 2-biased in ammatory response as well as the development of eosinophilic in ammation in nasal polyps [51,62,63]. While Kanagalingam S et al pointed out that obesity did not affect the severity of sinonasal diseases in asthma patients, which is paradoxical with our results [64].…”
Section: Discussioncontrasting
confidence: 75%
“…Of note, treatment of these cells with the mitochondria-targeted antioxidant mitoquinone (mitoQ) significantly decreased the IL-1β and NLRP3 expression that was induced by leptin, suggesting that this adipokine could lead to lung damage through mtROS-NLRP3 signalling [110]. These in vitro findings are consistent with studies conducted in individuals with airway inflammation, where serum levels of both leptin and IL-1β were shown to increase with BMI and were thus higher in subjects with obesity [114].…”
Section: Impairment Of the Nlrp3 Inflammasome In Obesity Leads To Pul...supporting
confidence: 81%
“…Focusing research on subjects with both airway inflammation and obesity, recent studies have shown that IL-1β serum and sputum levels are correlated with BMI and are an important risk factor for the exacerbation of symptoms [114,117]. However, a broad spectrum of other cytokines has also been found to be altered in obesity-related lung diseases.…”
Section: Impairment Of the Nlrp3 Inflammasome In Obesity Leads To Pul...mentioning
confidence: 99%
“…In addition, obesity has an impact on a variety of allergic diseases, including allergic rhinitis, obesity/overweight is identified as a risk factor for AR in children. 21 It is necessary to control the BMI of allergic patients within the normal range. 22 Green et al reported that people who had been diagnosed with allergic rhinitis were exposed to a deteriorating environment for a long time, and the symptoms became worse.…”
Section: Discussionmentioning
confidence: 99%